2019
DOI: 10.1038/s41538-019-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

An enzymatically controlled mucoadhesive system for enhancing flavour during food oral processing

Abstract: While a good mucoadhesive biopolymer must adhere to a mucus membrane, it must also have a good unloading ability. Here, we demonstrate that the biopolymer pullulan is partially digested by human salivary α-amylase, thus acting as a controlled release system, in which the enzyme triggers an increased release of flavour. Our oral processing simulations have confirmed an increase in the bioavailability of aroma and salt compounds as a function of oral pullulan degradation, although the release kinetics suggest a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The carboxymethylcellulose (CMC) and pullulan samples were purchased from Carbosynth, UK. DMAE-pullulan was obtained as described previously [30]. Briefly, 5 g of pullulan was dissolved in 25 ml of distilled water and mixed with a 25 mL 10 M sodium hydroxide solution.…”
Section: Methodsmentioning
confidence: 99%
“…The carboxymethylcellulose (CMC) and pullulan samples were purchased from Carbosynth, UK. DMAE-pullulan was obtained as described previously [30]. Briefly, 5 g of pullulan was dissolved in 25 ml of distilled water and mixed with a 25 mL 10 M sodium hydroxide solution.…”
Section: Methodsmentioning
confidence: 99%
“…In-mouth interactions between volatiles and salivary components are also known to occur which may influence extent of aroma release, through binding or enzymatic conversion ( Ployon et al, 2017 ). Pagès-Hélary et al (2014) found that both mucin and α-amylase have the ability to retain aroma molecules within saliva, and these findings were recently supported by Dinu, Gadon, et al (2019) . A significantly greater PSR in the HF group, along with greater amylase activity, may have facilitated greater protein-aroma binding and therefore contributed to the relatively lower in-mouth aroma release in the HF group.…”
Section: Discussionmentioning
confidence: 80%
“… Buttner et al (2002) illustrated that between 30% and 40% of aroma compounds can be retained on the oral and pharyngeal mucosa. In fact, mucoadhesive polymers have been proposed as a method to prolong the residence time, and therefore perception, of flavour compounds on oral surfaces ( Cook et al, 2017 ; Dinu et al, 2019 , Dinu et al, 2019 ). In the same way the LF group may have been less able to clear the drying proteins from the mouth, flavour compounds are likely to have persisted to a greater extent in-between sips leading to the significantly higher aftertaste perception.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that some of the lost functionality of ethanol may be tackled by the addition of dextrins or glycerol which can act as ‘ethanol-mimics’ and help increase aldehyde retention 10 . Further research into oral mucoadhesive might become an attractive option in beer reformulation, by modulating an increase in the retention of more hydrophobic compounds 50 . As observed in Dinu et al 50 the development of oral mucoadhesives can lead to a decrease in the interactions of aroma compounds with α-amylase.…”
Section: Discussionmentioning
confidence: 99%
“…Further research into oral mucoadhesive might become an attractive option in beer reformulation, by modulating an increase in the retention of more hydrophobic compounds 50 . As observed in Dinu et al 50 the development of oral mucoadhesives can lead to a decrease in the interactions of aroma compounds with α-amylase. Balancing these effects could provide brewers with significant guidance on the development of a NAB base recipe, in order to reduce the effects of beer dealcoholisation.…”
Section: Discussionmentioning
confidence: 99%